(3cJGH GdEeGe jMji Hf MeRI Edi SdWGf Gdjef hcJH CNQi dgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Edi GdebGe GdCYR GdCced GdeLGgO SdWGf Gdjef Sdjd Gdedhc s
(3BNQgG (B:s
(3Ef GQjO ZdG GdCUdGM eG ESJWYJ heG Jhajbi EdG HGddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B10) s
Keywords: (3GdJhMjO hGdedd hGdfMds